Arthroscopic Removal of Suprapatellar Fibroma of Tendon Sheath - Lou, Nan; Fang, Christian; Leung, Frankie; Cheung, Florence; Wong, Tak Man (The Surgery Journal, 2017)
Intra-articular fibroma of tendon sheath is a rare disease. To our knowledge, less than 20 cases have been reported in the literature, and none of them was a Chinese patient. In this case report, we present a Chinese patient with intra-articular fibroma of tendon sheath of the knee joint which was excised arthroscopically. We also summarized the clinical presentation, diagnosis, and subsequent management of intra-articular fibroma of tendon sheath.
Keywords: intra-articular fibroma; fibroma of tendon sheath; knee joint; arthroscopy